2019
DOI: 10.1507/endocrj.ej18-0532
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iodine is increased in papillary thyroid carcinoma but is not altered by regional population iodine intake status: a meta-analysis and implications

Abstract: Excessive iodine intake has been associated with increased risk of thyroid cancer (TC) in many studies, but the results have not been consistent. Since it was common knowledge that urinary iodine (UI) is considered a sensitive marker of current iodine intake, we conducted a meta-analysis to clarify the association between high UI and TC. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, and the Cochrane Collaboration. Betweengroup meta-analyses were performed to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Many previous studies have assessed the association between thyroid cancer and UIC, but some studies have focused on the median difference in UIC between cases and controls [ 25 , 26 ]. Although a meta-analysis reported the ORs for PTC relative to normal controls associated with excessive iodine intake [ 27 ], we could not directly compare their results with our study for the following reasons: two studies published in Chinese could not identify the method; for another study, the OR reported in the meta-analysis was not reported in the original article [ 27 ]; and the fourth study used a UIC reference value that differed from World Health Organization (WHO) standards [ 27 ]. In one study the PTC risk associated with an excessive UIC did not differ significantly between cases and controls [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have assessed the association between thyroid cancer and UIC, but some studies have focused on the median difference in UIC between cases and controls [ 25 , 26 ]. Although a meta-analysis reported the ORs for PTC relative to normal controls associated with excessive iodine intake [ 27 ], we could not directly compare their results with our study for the following reasons: two studies published in Chinese could not identify the method; for another study, the OR reported in the meta-analysis was not reported in the original article [ 27 ]; and the fourth study used a UIC reference value that differed from World Health Organization (WHO) standards [ 27 ]. In one study the PTC risk associated with an excessive UIC did not differ significantly between cases and controls [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Huang et al (34) showed excess urinary iodine concentrations in 44.3% of PTC patients compared to 22.2% of persons without PTC. Results of a few more studies demonstrated that urinary iodine levels in PTC patients were higher than those of healthy individuals (18,25,30).…”
Section: Discussionmentioning
confidence: 99%
“…This was because the subjects consumed iodine-rich foods (kelp or soup stock) on at least one or more days of the 16 days. Yan et al's (25) study mentioned that high iodine intake is not a risk factor for PTC and that high urinary iodine is just a specific characteristic of this disease. Iodine retention was found in urinary iodine even with a large single dose iodine administration, e.g., oral administration or injection of iodinated contrast (about 30 grams of iodine), and the urinary iodine levels were transiently increased after receiving iodinated contrast and soon reverted back to baseline either in euthyroid subjects or in PTC patients regardless of thyroidectomy operation (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Another research suggests that high iodine intake could be linked to the growth of PTC rather than its initiation [ 31 ]. A meta-assessment of 22 cross-sectional studies conducted by Yan et al indicates that high iodine intake does not pose a risk for PTC development and that high urinary iodine is a specific characteristic of the disease [ 36 ]. Some studies have identified associations between excessive iodine intake and elevated risks of lymph node metastasis, larger tumors, peritumoral invasion, bilateral tumor location, and extra-thyroidal metastases.…”
Section: Discussionmentioning
confidence: 99%